THERMO-MECHANICAL MODELLING OF BLACK SEA BASIN (DE) FORMATION - Cloetingh S.; Spadini G.; Van Wees J.D.; Beekman F. (My University, 2003)
We present the results of a thermo-mechanical modelling study carried out to investigate the effect of pre-rift rheology on subsequent basin (de)formation in the Black Sea area. Important differences are inferred for the bulk lithosphere structure and mechanical properties, expressed in terms of different estimates for levels of necking in the western and eastern Black Sea, respectively. Gravity data provide constraints on the mode of flexure in the Black Sea, pointing to significant lateral variations in pre-rift lithospheric strength. These features strongly affect predictions for Mesozoic – Cenozoic Basin stratigraphy and have implications for the presence and development of rift shoulder topography on the margins of the Black Sea Basins. Differences in lithosphere strength affect the mode of stress propagation from the basin margins into the central parts of the Black Sea Basins during the post-rift phase. These post-rift compressional stresses could be of key importance for long-wavelength Late Neogene differential motions within the basins, superimposed on vertical motions induced by rifting and subsequent sediment loading. Thermo-mechanical modelling of integrated lithospheric strength points to a rapid increase of strength during the later stages of post-rift evolution and the presence of relatively strong lithosphere in the centre of the basin. These features predict preferential shortening induced by compressional activity of surrounding orogens to be primarily accommodated at the basins' margins.
Keywords: Thermo-mechanical modelling; Lithosphere memory; Black Sea; Intraplate stress; Neotectonics; Cenozoic::Neogene; Кайнозой::Неоген